Responses of Square and Triangular TLPs Subjected to Random Waves - M.A, Gasim (2008)

(untitled)
Tension leg platform (TLP) is a type of offshore platform suitable for petroleum exploration in deepwater. The dynamic responses of TLP such as the motions and the tether tensions when it is subjected to wave forces are needed for the design and maintenance of the structure. Limiting these responses leads to better stability and safe drilling operations. In this paper, a MATLAB program has been developed for determining the dynamic responses of square and triangular TLPs subjected to random waves. The structure has been considered as a rigid body and all the six motions have been determined. Linear Airy wave theory and Morison equation have been used for wave force calculations. Newmark Beta Method of time domain analysis has been used for the dynamic analysis. The response amplitude operators (RAO) for typical square and triangular TLPs have been compared with available theoretical results. The results have proved the capability of the developed programme in predicting the responses and have indicated that except for surge, the responses of triangular TLP are much higher than that of square TLP.